Extensive Antibiotic and Antimalarial Prescription Rate among Children with Acute Febrile Diseases in the Lake Victoria Region, Tanzania. (11th February 2021) - Huth, Philipp Florian Brixius; Addo, Marylyn; Daniel, Tim; Groendahl, Britta; Hokororo, Adolfine; Koliopoulos, Philip; Mshana, Stephen; Pretsch, Leah; Schmidt, Christian; Zuechner, Antke; Gehring, Stephan; Kayange, Neema
Abstract: Objectives: Acute mosquito-borne febrile diseases pose a threat to children in the Sub-Saharan-Africa with ∼272 000 children dying worldwide from malaria in 2018. Although the awareness for malaria in this area has increased due to improved health education, the apparent decline of actual malaria cases has not affected clinical practice significantly. This study collected clinical and epidemiologic data of children presenting with acute febrile diseases in order delineate their diagnostic and therapeutic management. Methods: A hospital-based cross-sectional clinical study was conducted at the Sekou Toure Regional Referral Hospital in Tanzania. Children between 1 month and 12 years of age with an axillary temperature ≥ 37.5°C were recruited from August 2016 to December 2016. Children received full clinical examination. In addition, file data about diagnostics and treatment were collected and malaria rapid diagnostic tests (mRDTs) were performed. Confirmatory malaria polymerase chain reaction was performed from dry blood spots. Results: From 1381 children presented in the pediatric outpatient department, 133 met the inclusion criteria. Out of 133 febrile children, 10.5% were malaria positive. Treatment data indicate the prescription of antimalarials in 35.3% and antibiotics in 63.9% of the children with an overlap of 24.1% receiving both. Despite a negative mRDT, 36 patients received antimalarials. Conclusions: The findings of this study confirm a significant decline of malaria cases in the Lake Victoria region. The discrepancy between the valuable results provided by mRDTs and the high prescription rates of antibiotics and antimalarials call for an enforced diagnostic and therapeutic algorithm. LAY SUMMARY: The aim of the study was to take a closer look at reported cases of febrile diseases in the Lake Victoria region and assess the relationship between clinical as well as diagnostic findings and the resulting therapeutic concept. Based on these findings the prescription rate of antimalarial and antibiotic drugs was analyzed. The results showed an overall high prescription rate of antimalarials and antibiotics in both diagnosed malaria cases and cases with diagnosed bacterial infections. Not only with regards to the possible side effects of these medications but also keeping in mind the apparent misuse of resources this practice poses a serious burden to the health care system in this low resource country.